Analysis of Design Flood Discharge and Water Level Case Study of the Batang Singkut River Section Sarolangun Regency - Fitria Melany; Harmes Harmes; Freddy Ilfan (Politeknik Negeri Batam, 2022)
The Batang Singkut River section is a tributary of the Batang Asai River which passes through Pelawan District and Singkut District. This research was carried out by calculating the design flood discharge and modeling the water level using HEC-RAS. The starting point of the research is on the bridge around the Jambi University campus in Sarolangun Regency with the length of the river under review being 300 meters. The discharge data used is the maximum daily discharge for 10 years from 2011 to 2020. The method used to calculate the design flood discharge is the method of frequency analysis and distribution testing using the chi-square method. The analysis was carried out to find the design flood discharge frequency using the Pearson III log distribution type for return periods of 2 and 5 years. The calculated discharge is entered into the HEC-RAS to model the water level. The modeling results showthat at a 2-year return period for cross sections STA 0+00, STA 1+00, STA 1+50, STA 2+00, STA 2+50, and STA 3+00 are able to accommodate water with a discharge of 83.5026 m3/s, but for the STA 0+50 cross section it is unable to accommodate the amount of discharge generated. Whereas for the return period of 5 years the cross section of STA 0+00 to STA 2+50 is unable to accommodate water with a discharge of 118.4132 m3/s, while for STA 3+00 the cross section can hold water.